A low-Cr and high-corrosion-resistant FeCrAl-based alloy and preparation method thereof

By controlling the Cr and Al content in the FeCrAl base alloy, and using high-temperature solid solution, low-temperature rolling and two-pass annealing heat treatment processes, an alloy with excellent corrosion resistance and radiation resistance was prepared, and the existing FeCrAl base was solved. The lack of performance of alloys under high temperature and high pressure water environment and high dose neutron radiation.

CN118726857BActive Publication Date: 2025-02-21SHANGHAI JIAOTONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411063983.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-05
Publication Date
2025-02-21
Estimated Expiration
2044-08-05

AI Technical Summary

Technical Problem

The existing FeCrAl-based alloy materials cannot meet the requirements of core structures such as nuclear reactor fuel cladding and lattice for high-temperature and high-pressure water environment corrosion and high-dose neutron radiation.

Method used

Through the interaction between alloy elements, combined with high-temperature solid solution, low-temperature rolling and two-pass annealing heat treatment processes, FeCrAl-based alloys with Cr content between 10.0-12.0% and Al content between 4.3-5.5% were prepared to form different crystals Alloys in particle state improve their corrosion resistance and radiation resistance.

Benefits of technology

The alloy is significantly better than the corrosion resistance of existing serviced materials under a high temperature water vapor environment of 1000°C, and has excellent room temperature and high temperature mechanical properties, which reduces energy consumption and preparation costs and increases the commercial value of FeCrAl base alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118726857B_ABST
    Figure CN118726857B_ABST
Patent Text Reader

Abstract

The present invention discloses a low-Cr and highly corrosion-resistant FeCrAl-based alloy and a preparation method thereof, belonging to the technical field of new structural materials. The lower Cr content in the FeCrAl-based alloy disclosed in the present invention can enhance the toughness of the alloy and significantly reduce the radiation embrittlement phenomenon of the fuel cladding tube under high-intensity neutron irradiation. At the same time, the high-density solid solution second phase in the FeCrAl-based alloy has the characteristics of capturing radiation defects and inhibiting radiation damage, and has very excellent high-temperature radiation damage resistance. The low-Cr and highly corrosion-resistant FeCrAl-based alloy prepared by the present invention has better uniform corrosion performance under normal working conditions and high-temperature corrosion resistance in a high-temperature water vapor environment than existing service materials. The alloy prepared by the present invention has very high mechanical properties and thermal stability of the structure at high temperatures.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new structural materials, and in particular relates to a low-Cr and highly corrosion-resistant FeCrAl-based alloy and a preparation method thereof. Background Art

[0002] The nuclear industry has extremely high requirements on the accident tolerance and related serviceability of the fuel cladding materials of nuclear reactors, among which the corrosion resistance at room and high temperature conditions is particularly important.

[0003] Traditional nuclear reactor fuel cladding materials are zirconium alloy materials, which have excellent service performance, but their accident tolerance rate is very low. When an accident occurs, zirconium alloy contacts high-temperature water vapor and quickly produces a large amount of hydrogen and triggers a hydrogen explosion, which brings great hidden dangers. Therefore, the nuclear industry will put the development of FeCrAl-based alloys with higher accident tolerance on the agenda. The addition of Cr and Al elements in the alloy can significantly improve the corrosion resistance of the material. It is generally believed that when the Cr content reaches more than 20%, the alloy can form a continuous and dense protective oxide layer on the surface when encountering corrosive media. However, for the service environment of the cladding tube, it not only needs to withstand the corrosion of the high-temperature and high-pressure water environment during its service, but also requires it to be able to withstand the high-dose neutron irradiation produced by fuel fission.

[0004] There is an urgent need in the art for a FeCrAl-based alloy that can withstand corrosion in a high-temperature, high-pressure water environment and withstand high-dose neutron irradiation generated by fuel fission. Summary of the invention

[0005] The purpose of the present invention is to provide a low-Cr and highly corrosion-resistant FeCrAl-based alloy and a preparation method thereof, so as to solve the problem that the FeCrAl-based alloy materials in the prior art cannot meet the requirements for core structures such as fuel element cladding and grids. The present invention obtains alloys with different grain states through the interaction between alloy elements, combined with high-temperature solid solution, low-temperature rolling and two-pass annealing heat treatment processes. The alloy has excellent corrosion resistance under normal service conditions, and its corrosion resistance is significantly better than that of existing service materials in a high-temperature water vapor environment of 1000°C.

[0006] One of the technical solutions provided by the present invention:

[0007] A low-Cr and high-corrosion-resistant FeCrAl-based alloy comprises the following components by mass percentage: Cr: 10.0-12.0%, Al: 4.3-5.5%, Mo: 1.8-2.6%, Nb: 1.0-1.5%, Si: 0.1-0.3%, Ta: 0.1-0.2%, Zr: 0.1-0.3%, Y: 0.05-0.1%, C: ≤0.008%, N: ≤0.005%, O: ≤0.003%, and the balance is iron and unavoidable impurities.

[0008] The low-Cr and highly corrosion-resistant FeCrAl-based alloy provided by the present invention also contains impurities, and the impurity content meets the standards of current commercial industrial pure iron and ferritic stainless steel. The impurity content is not discussed in the present invention and is therefore ignored.

[0009] Preferably, the total mass percentage content of the Cr, Al and Si alloying elements is not less than 14.5%, so as to maintain the good room temperature mechanical strength of the FeCrAl-based alloy. At the same time, in order to prevent the FeCrAl-based alloy from having aggravated hardening and radiation embrittlement tendency, which causes brittle fracture of the alloy during reactor operation and processing and preparation, the content of Cr and Al should be strictly controlled and reduced on the basis of ensuring that the FeCrAl-based alloy has good resistance to high-temperature steam oxidation. The mass percentage content of the Cr element in the present invention is ≤12.0%.

[0010] Preferably, the total mass percentage content of the Zr and Y alloy elements is ≥ 0.25%, so as to synergistically improve the high temperature oxidation resistance of the alloy.

[0011] Preferably, the total mass percentage content of Mo, Nb, Si and Ta is ≥3%, so that a large number of dispersed Laves second phase particles can be precipitated to improve the room temperature mechanical properties and high temperature strength of the alloy.

[0012] The second technical solution provided by the present invention is:

[0013] A method for preparing the above-mentioned low-Cr and highly corrosion-resistant FeCrAl-based alloy comprises the following steps: weighing each alloy element component according to mass percentage to form a steel billet, hot-rolling the steel billet for multiple passes, then subjecting the hot-rolled plate to high-temperature solid solution treatment, low-temperature rolling and two-pass annealing treatment, taking it out and cooling it to room temperature to prepare the low-Cr and highly corrosion-resistant FeCrAl-based alloy.

[0014] Preferably, the high temperature solid solution is carried out at a temperature of 1150-1250°C and for a time of 1.5-3.0 hours.

[0015] Preferably, the low temperature rolling is warm rolling at 420° C. to a specified thickness, with a rolling ratio of 65%, air cooling after rolling, and then straightening by cold rolling.

[0016] Preferably, the two annealing heat treatments include: a first high-temperature annealing temperature of 1130-1170°C, an annealing time of 15-20s, and then water cooling; a second low-temperature annealing temperature of 600-650°C, an annealing time of 30-60min, and air cooling to room temperature after taking out.

[0017] The present invention controls the size of grains and precipitated phases through an optimal two-pass annealing process, thereby synergistically improving the strength and toughness of the alloy. By controlling the temperature and time of the two-pass annealing treatment, a low-Cr FeCrAl-based alloy with excellent strength, toughness and corrosion resistance is prepared, which has excellent room temperature strength and room temperature toughness, excellent service performance under normal working conditions and accident conditions, and can significantly reduce energy consumption and preparation costs. The alloy prepared by this method has excellent uniform corrosion performance under normal service conditions, excellent oxidation resistance in a high-temperature water vapor environment of 1000°C, and has high mechanical strength and high toughness at room temperature and 400°C. It has excellent comprehensive performance, further improving the commercial value of FeCrAl-based alloys.

[0018] The third technical solution provided by the present invention is:

[0019] An application of the above-mentioned low-Cr and highly corrosion-resistant FeCrAl-based alloy in the preparation of nuclear reactor fuel cladding materials, aircraft engine structural materials or power plant steam pipe structural materials.

[0020] Compared with the prior art, the present invention has the following advantages and technical effects:

[0021] The present invention further controls the range of Cr and Al content by controlling the range of alloying element components of Cr, Al, Mo, Nb, Si, Ta, Zr and Y, thereby avoiding the problem of severe hardening and embrittlement in FeCrAl-based alloy materials under thermal aging and irradiation conditions of reactor operation conditions, and at the same time ensuring excellent corrosion resistance under service conditions; appropriate amounts of microalloying elements such as Mo, Nb, Si, Ta, Zr and Y and appropriate heat treatment processes can not only refine the FeCrAl-based alloy matrix grains, significantly improve the strength and plasticity of the alloy at room temperature, but also significantly improve the recrystallization temperature and high-temperature strength of the alloy at high temperatures, so that the structural stability of the alloy at high temperatures is significantly improved, and at the same time, the element diffusion fast channel brought by the subgrain boundary can contribute to the formation of a uniform surface oxide layer in the early stage of corrosion, further improving the corrosion resistance of the alloy. By controlling the composition of the alloying element mass percentage and combining the heat treatment process, an alloy in a river-like grain state is obtained, and a fine and dispersed Laves second phase is distributed at the subgrain boundary in the finished alloy, which significantly improves the mechanical properties of the alloy such as room temperature toughness and high-temperature strength.

[0022] The lower Cr content in the FeCrAl-based alloy disclosed in the present invention can enhance the toughness of the alloy and significantly reduce the radiation embrittlement phenomenon of the fuel cladding tube under high-intensity neutron irradiation. At the same time, the high-density solid solution second phase in the FeCrAl-based alloy has the characteristics of capturing radiation defects and inhibiting radiation damage, and has very excellent high-temperature radiation damage resistance. The low-Cr and highly corrosion-resistant FeCrAl-based alloy prepared by the present invention has better uniform corrosion performance under normal working conditions and high-temperature corrosion resistance in high-temperature water vapor environment than existing service materials, and the alloy has very high mechanical properties and thermal stability of the structure at high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0024] Figure 1 This is a cross-sectional view of the oxide film of the FeCrAl-based alloy prepared in Example 1 after uniform corrosion for 4000 hours in a high-temperature and high-pressure water environment;

[0025] Figure 2 The results of high temperature oxidation performance test of the FeCrAl-based alloys with low Cr content and high corrosion resistance prepared in Examples 1-3 of the present invention and the alloys of Comparative Examples 1-2 in a 1000° C. high temperature steam environment;

[0026] Figure 3 Mechanical tensile curves at room temperature for the FeCrAl-based alloy with low Cr and high corrosion resistance prepared in Example 3 and the alloys provided in Comparative Examples 7 and 8;

[0027] Figure 4 The mechanical properties of the low-Cr and highly corrosion-resistant FeCrAl-based alloys prepared in Example 3, Comparative Example 7 and Comparative Example 8 under different test temperature conditions are compared;

[0028] Figure 5 This is a SEM picture of the low-Cr and highly corrosion-resistant FeCrAl-based alloy prepared in Example 1, which contains a large number of subgrain boundary grains;

[0029] Figure 6 This is a TEM image of the precipitation phase of the FeCrAl-based alloy with low Cr and high corrosion resistance prepared in Example 1;

[0030] Figure 7 TEM image of the FeCrAl-based alloy precipitate phase prepared in Comparative Example 7;

[0031] Figure 8 This is the TEM image of the precipitation phase of the FeCrAl-based alloy prepared in Comparative Example 8. DETAILED DESCRIPTION

[0032] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0033] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0034] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0035] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0036] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0037] The room temperature in the present invention refers to 25±2°C.

[0038] In addition, unless otherwise specified, % in Examples and Comparative Examples is based on mass.

[0039] An embodiment of the present invention provides a low-Cr and highly corrosion-resistant FeCrAl-based alloy. The low-Cr and highly corrosion-resistant FeCrAl-based alloy includes the following components, measured by mass percentage: Cr: 10.0-12.0%, Al: 4.3-5.5%, Mo: 1.8-2.6%, Nb: 1.0-1.5%, Si: 0.1-0.3%, Ta: 0.1-0.2%, Zr: 0.1-0.3%, Y: 0.05-0.1%, C: ≤0.008%, N: ≤0.005%, O: ≤0.003%, and the remainder is iron and unavoidable impurities, and the impurity content meets the current standards of commercial industrial pure iron and ferritic stainless steel.

[0040] In some preferred embodiments of the present invention, the total weight percentage content of the Cr, Al and Si alloying elements is not less than 14.5% so as to maintain good high-temperature oxidation performance and corrosion resistance; the mass percentage content of the Cr element is ≤12.0% so as to reduce the radiation embrittlement tendency of the alloy under actual service conditions; the total weight percentage content of the Mo, Nb, Si and Ta alloying elements is not less than 3% so as to precipitate a large number of dispersed Laves second phase particles and improve the room temperature mechanical properties and high temperature strength of the alloy; the total mass percentage content of the Zr and Y alloying elements is ≥0.25% so as to synergistically improve the high-temperature oxidation resistance of the alloy.

[0041] The embodiment of the present invention also provides a method for preparing the above-mentioned low-Cr and highly corrosion-resistant FeCrAl-based alloy, wherein the test alloy elements are prepared into a steel billet according to the mass percentage of the chemical composition, and the steel billet is hot-forged and then hot-rolled, wherein the initial forging temperature is not less than 1000°C and the final forging temperature is not less than 900°C. After forging, the steel billet is hot-rolled at a temperature of 800°C and a rolling ratio of 40%, followed by high-temperature homogenization annealing and warm rolling, and the hot-rolled steel plate is heated to 1150-1250°C, solution treated for 1.5-3.0h, and rolled to a set thickness at 420°C with a rolling ratio of 65%, air-cooled after rolling, and then cold-rolled and straightened before two annealings are performed, the first high-temperature annealing temperature is 1130-1170°C, the annealing time is 15-20s, and then water-cooled; then a second low-temperature annealing is performed, the low-temperature annealing temperature is 600-650°C, and the annealing time is 30-60min. It is then taken out and air-cooled to room temperature, which prevents the growth of Laves second phase particles during processing and heat treatment, and obtains fine second phase particles densely precipitated on the subgrain boundaries, ensuring the room temperature and high temperature strengthening effect of the alloy. At the same time, a large number of subgrain boundaries help the diffusion of elements in the early stage of corrosion oxide film formation, making it easier to form a uniform and dense protective oxide layer on the alloy surface, which helps to improve its corrosion resistance.

[0042] Examples 1-3 of the present invention and Comparative Examples 1 and 3-6 respectively selected different element ratios within a certain range of the composition of the invention to prepare alloys, and the subsequent heat treatment process remained consistent. Comparative Example 2 was a commercial Zr-4 alloy (purchased from State Power Investment Corporation National Nuclear Zirconium Industry), and Comparative Examples 7-8 were used to compare the effects of changes in the two heat treatment processes on the properties of the alloy.

[0043] Table 1 shows the metal element composition ratios of the FeCrAl alloys with low Cr and high corrosion resistance prepared in Examples 1-3 of the present invention and the alloys in Comparative Examples 1-8.

[0044] Table 1

[0045]

[0046] Example 1 Preparation method of a low-Cr and high-corrosion-resistant FeCrAl-based alloy

[0047] Alloy element composition: by mass percentage, including the following components: Cr: 10.1%, Al: 4.9%, Mo: 2.3%, Nb: 1.2%, Si: 0.2%, Ta: 0.15%, Zr: 0.18%, Y: 0.08%, C: ≤0.008%, N: ≤0.005%, O: ≤0.003%, the balance is iron and unavoidable impurities.

[0048] Preparation method: weighing each alloy element according to the above mass percentage to prepare a steel billet, hot forging the steel billet and then hot rolling, wherein the initial forging temperature is not less than 1000°C, and the final forging temperature is not less than 900°C, the steel billet is hot rolled after forging, the hot rolling temperature is 800°C, the rolling ratio is 40%, and then high-temperature homogenization annealing and warm rolling are performed, the hot-rolled plate is heated to 1200°C for solution for 2h, rolled to a set thickness at 420°C, the rolling ratio is 65%, air-cooled after rolling, and then cold-rolled and straightened and two annealings are performed: the first high-temperature annealing process is 1150°C / 20s, and then water-cooled; then a second low-temperature annealing is performed, the second low-temperature annealing process is 600°C / 30min, and then taken out and air-cooled to room temperature to prepare the FeCrAl-based alloy with low Cr and high corrosion resistance.

[0049] Example 2 Preparation method of a low-Cr and high-corrosion-resistant FeCrAl-based alloy

[0050] Alloy element composition: by mass percentage, including the following components: Cr: 10.9%, Al: 4.7%, Mo: 1.8%, Nb: 1.5%, Si: 0.28%; Ta: 0.12%, Zr: 0.16%, Y: 0.09%, C: ≤0.008%, N: ≤0.005%, O: ≤0.003%, the balance is iron and unavoidable impurities.

[0051] Preparation method: weighing each alloy element according to the above mass percentage to prepare a steel billet, hot forging the steel billet and then hot rolling, wherein the initial forging temperature is not less than 1000°C, and the final forging temperature is not less than 900°C, the steel billet is hot rolled after forging, the hot rolling temperature is 800°C, the rolling ratio is 40%, and then high-temperature homogenization annealing and warm rolling are performed, the hot-rolled plate is heated to 1250°C for solution treatment for 1.5 hours, rolled to a set thickness at 420°C, the rolling ratio is 65%, air-cooled after rolling, and then cold-rolled and straightened and annealed in two passes: the first high-temperature annealing process is 1170°C / 15s, followed by water cooling; then a second low-temperature annealing is performed, the second low-temperature annealing process is 630°C / 60min, and then taken out and air-cooled to room temperature to prepare the FeCrAl-based alloy with low Cr and high corrosion resistance.

[0052] Example 3 Preparation method of a low-Cr and high-corrosion-resistant FeCrAl-based alloy

[0053] Alloy element composition: by mass percentage, including the following components: Cr: 11.7%, Al: 4.4%, Mo: 2.3%, Nb: 1.3%, Si: 0.23%, Ta: 0.18%, Zr: 0.11%, Y: 0.06%, C: ≤0.008%, N: ≤0.005%, O: ≤0.003%, the balance is iron and unavoidable impurities.

[0054] Preparation method: weighing each alloy element according to the above mass percentage to prepare a steel billet, hot forging the steel billet and then hot rolling, wherein the initial forging temperature is not less than 1000°C, and the final forging temperature is not less than 900°C, the steel billet is hot rolled after forging, the hot rolling temperature is 800°C, the rolling ratio is 40%, and then high-temperature homogenization annealing and warm rolling are performed, the hot-rolled plate is heated to 1150°C for solution for 3h, rolled to a set thickness at 420°C, the rolling ratio is 65%, air-cooled after rolling, and then cold-rolled and straightened and two annealings are performed: the first high-temperature annealing process is 1130°C / 20s, followed by water cooling; then a second low-temperature annealing is performed, the second low-temperature annealing process is 650°C / 30min, and then taken out and air-cooled to room temperature to prepare the FeCrAl-based alloy with low Cr and high corrosion resistance.

[0055] Comparative Example 1

[0056] In order to compare the uniform corrosion and high temperature steam oxidation resistance with Examples 1 and 3, Comparative Example 1 was set.

[0057] Alloy element composition: by mass percentage, including the following components: Cr: 13.3%, Al: 4.5%, Mo: 2.1%, Nb: 0.5%, Si: 0.2%, C: ≤0.008%, N: ≤0.005%, O: ≤0.003%, and the balance is iron and unavoidable impurities.

[0058] The preparation method is the same as Example 1.

[0059] Comparative Example 2

[0060] Commercial Zr-4 alloy is selected to measure the uniform corrosion and high temperature water vapor corrosion resistance of the FeCrAl-based alloy prepared in the present invention and the existing commercial zirconium alloy. The composition ratio of the commercial Zr-4 alloy is Fe: 0.21%, Cr: 0.12%, Al: 0.0033%, Si: 0.009%, C: ≤0.008%, N:

[0061] ≤0.018%, O: 0.13%, and the rest are Zr elements and other impurities that meet the standards of commercial Zr-4 alloy.

[0062] Comparative Example 3

[0063] In order to demonstrate the effect of the content of alloying element Cr on the corrosion performance of FeCrAl-based alloy, Comparative Example 3 was set.

[0064] Alloy element composition: by mass percentage, including the following components: Cr: 6.9%, Al: 4.8%, Mo: 2.1%, Nb: 1.4%, Si: 0.22%; Ta: 0.14%, Zr: 0.13%, Y: 0.09%, C: ≤0.008%, N: ≤0.005%, O: ≤0.003%, the balance is iron and unavoidable impurities.

[0065] The preparation method is the same as Example 1.

[0066] Comparative Example 4

[0067] In order to demonstrate the influence of alloying element Al on the corrosion performance of FeCrAl-based alloy, comparative example 4 is set. Alloying element composition: by mass percentage, including the following components: Cr: 11.7%, Al: 2.4%, Mo: 2.1%, Nb: 1.0%, Si: 0.20%, Ta: 0.14%, Zr: 0.13%, Y: 0.07%, C:

[0068] ≤0.008%, N: ≤0.005%, O: ≤0.003%, the balance is iron and unavoidable impurities.

[0069] The preparation method is the same as Example 1.

[0070] Comparative Example 5

[0071] In order to demonstrate the effects of alloying elements Mo, Nb, Si and Ta on the corrosion properties of FeCrAl-based alloys, Comparative Example 5 was set.

[0072] Alloy element composition: by mass percentage, including the following components: Cr: 10.5%, Al: 5.1%, Zr: 0.16%, Y: 0.09%, C: ≤0.008%, N: ≤0.005%, O: ≤0.003%, and the balance is iron and unavoidable impurities.

[0073] The preparation method is the same as Example 1.

[0074] Comparative Example 6:

[0075] In order to demonstrate the effects of alloying elements Zr and Y on the high temperature water vapor corrosion performance of FeCrAl-based alloys, comparative example 6 was set.

[0076] Alloy element composition: by mass percentage, including the following components: Cr: 11.4%, Al: 5.2%, Mo: 1.9%, Nb: 1.3%, Si: 0.24%, Ta: 0.13%, C: ≤0.008%, N: ≤0.005%, O: ≤0.003%, the balance is iron and unavoidable impurities.

[0077] The preparation method is the same as Example 1.

[0078] In order to demonstrate the influence of high temperature annealing parameters on the mechanical properties of FeCrAl alloy in the two-pass annealing process, Comparative Examples 7 and 8 were set.

[0079] Comparative Example 7:

[0080] Alloy element composition: by mass percentage, including the following components: Cr: 11.7%, Al: 4.4%, Mo: 2.3%, Nb: 1.3%, Si: 0.23%, Ta: 0.18%, Zr: 0.11%, Y: 0.06%, C: ≤0.008%, N: ≤0.005%, O: ≤0.003%, the balance is iron and unavoidable impurities.

[0081] Preparation method: weigh each alloy element according to the above mass percentage to prepare a steel billet, perform multiple hot rolling on the steel billet, heat the hot-rolled plate to 1200°C for solution treatment for 2 hours, roll it to a set thickness at 420°C, with a rolling ratio of 65%, air-cool it after rolling, and then perform two annealings after cold rolling and straightening: the first high-temperature annealing process is 1150°C / 5min, followed by water cooling; then perform a second low-temperature annealing process at 600°C / 30min, then take it out and air-cool it to room temperature, and prepare the FeCrAl-based alloy with low Cr and high corrosion resistance.

[0082] Comparative Example 8

[0083] Alloy element composition: by mass percentage, including the following components: Cr: 11.7%, Al: 4.4%, Mo: 2.3%, Nb: 1.3%, Si: 0.23%, Ta: 0.18%, Zr: 0.11%, Y: 0.06%, C: ≤0.008%, N: ≤0.005%, O: ≤0.003%, the balance is iron and unavoidable impurities.

[0084] Preparation method: weighing each alloy element according to the above mass percentage to prepare a steel billet, hot forging the steel billet and then hot rolling, wherein the initial forging temperature is not less than 1000°C, and the final forging temperature is not less than 900°C, the steel billet is hot rolled after forging, the hot rolling temperature is 800°C, and the rolling ratio is 40%, then the hot-rolled steel plate is heated to 1200°C for solution treatment for 2h, rolled to a set thickness at 420°C, the rolling ratio is 65%, air-cooled after rolling, and then cold-rolled and straightened and annealed in two passes: the first high-temperature annealing process is 1150°C / 20s, followed by water cooling; then a second low-temperature annealing is performed, the second low-temperature annealing process is 800°C / 30min, and then taken out and air-cooled to room temperature to prepare the FeCrAl-based alloy with low Cr and high corrosion resistance.

[0085] The corrosion resistance of the alloys of Examples 1-3 and Comparative Examples 1-9 was measured by sampling and weighing at intervals and in-situ high-temperature water vapor corrosion test methods, and the mechanical properties of the above alloys were measured using a universal material testing machine. Table 2 shows the corrosion resistance and mechanical properties of the above alloys, where the normal service test conditions are: 360°C, 20.0Mpa, 200ppb DO high-temperature and high-pressure water environment. The conditions of the high-temperature water vapor corrosion test are: 1000°C high-temperature water vapor atmosphere, and an argon carrier gas flow rate of 50mL / min.

[0086] Table 2

[0087]

[0088] Comparative Example 9

[0089] According to Example 4 of a heat treatment method for a low-Cr and high-toughness alloy in patent CN 117187705 B, a low-Cr and high-toughness alloy is prepared. The composition ratio of the optimal embodiment is Cr: 12.8%, Al: 4.3%, Mo: 2.0%, Nb: 1.0%, Si: 0.15%, V: 0.15%, Hf: 0.15%, Ga: 0.1%, Ni: 0.15%, La: 0.05%, C: ≤0.008%, N: ≤0.005%, O: ≤0.003%, and the balance is iron. The impurity content meets the current standards of commercial industrial pure iron and ferritic stainless steel, and the two-pass annealing process is 1100℃-30s-550℃-120min. Compared with the prior art, the present invention has a lower Cr content in the alloy, which helps to improve the radiation resistance of the FeCrAl-based alloy, and the optimized heat treatment process significantly shortens the time required for the heat treatment process. The addition of Y and Zr elements significantly improves its resistance to high-temperature water vapor oxidation.

[0090] Performance test experiment:

[0091] 1. Uniform corrosion performance test

[0092] The uniform corrosion test in the present invention is carried out in an autoclave with 316 stainless steel as the substrate, and the key experimental parameters are controlled as follows: the test temperature is 360°C, the ultrapure water pressure is 20.0Mpa, the dissolved oxygen DO is 200ppb, and the cooling water return flow rate is 6-8L / h, so as to ensure that the corrosion products are flushed in time and will not feedback and affect the uniform corrosion environment.

[0093] The FeCrAl-based alloy prepared in Example 1 was uniformly corroded in a high-temperature and high-pressure water environment of 360°C, 20.0 MPa, and 200 ppb DO for 4000 hours. Figure 1 The cross-sectional view of the oxide film of the FeCrAl-based alloy prepared in Example 1 after being uniformly corroded for 4000 hours in a high-temperature and high-pressure water environment; Figure 1 It can be seen that after the alloy corrosion state stabilizes, a continuous and dense uniform oxide layer of 100-200nm is generated on the alloy surface, and as the oxidation time increases, the subsequent oxide film thickness no longer changes, indicating that the FeCrAl-based alloy prepared in this embodiment has a continuous and dense uniform oxide layer on the surface under normal service conditions of the pressurized water reactor cladding, and together with the inner Cr-rich oxide layer, it synergistically prevents further oxidation. The FeCrAl-based alloy prepared in this embodiment has extremely excellent uniform corrosion resistance. In addition, under the heat treatment process conditions specified in the present invention, the obtained alloy structure contains a large number of subgrain boundaries, which are caused by Figure 5 As shown, it promotes the diffusion of elements in the early stage of oxide film formation, helps the formation of a protective oxide layer on the surface, and further improves its corrosion resistance.

[0094] 2. High temperature steam oxidation performance

[0095] The present invention conducts a high temperature steam oxidation experiment on the FeCrAl-based alloy with low Cr and high corrosion resistance prepared in Examples 1-3 and the alloy of Comparative Examples 1-2 on a TGA device.

[0096] Figure 2 The high temperature oxidation performance test results of the FeCrAl-based alloys with low Cr and high corrosion resistance prepared in Examples 1-3 of the present invention and the alloys of Comparative Examples 1-2 in a 1000°C high temperature steam environment are shown in FIG. Figure 2 It can be seen that as the high-temperature steam oxidation time increases, the weight gain curve of the commercial Zr-4 alloy rises rapidly, while the weight gain of the FeCrAl-based alloys in the present invention (Example 1 (10.1Cr+4.9Al), Example 2 (10.9Cr+4.7Al) and Example 3 (11.7Cr+4.4Al)) is maintained at a relatively low level, indicating that the FeCrAl-based alloy prepared by the present invention has significant resistance to high-temperature oxidation and strong resistance to accident conditions. The measurement results of the FeCrAl-based alloy (13.3Cr+4.5Al) of Comparative Example 1 show that as the Cr content increases from 10% to 13%, the weight gain curve decreases and tends to be stable around 12%.

[0097] 3. Room temperature and high temperature mechanical properties test

[0098] According to GB / T 2975-2018 Steel and Steel Product Mechanical Properties Test Sampling Location and Sample Preparation Standard, the low-Cr and high-corrosion-resistant FeCrAl-based alloy prepared in Example 3 and the alloys of Comparative Examples 7 and 8 were subjected to room temperature tensile tests. Figure 4 The mechanical tensile curves of the FeCrAl-based alloy with low Cr and high corrosion resistance prepared in Example 3 and the alloys provided in Comparative Examples 7 and 8 at room temperature are shown in Table 1. Figure 4It can be seen that the material obtained by the two-pass annealing heat treatment process selected in Example 3 has better comprehensive mechanical properties. Too long high-temperature annealing time or too high low-temperature annealing temperature may lead to inappropriate growth of grain size or precipitation phase size, which will damage the comprehensive mechanical properties of the material.

[0099] Figure 3 The mechanical properties of the low-Cr and highly corrosion-resistant FeCrAl-based alloy prepared in Example 3 under different temperature conditions are compared, where Rm is the tensile strength obtained by mechanical testing, Rp is 0.2 is the specified non-proportional extension strength (yield strength) obtained by the test, and A% is the elongation at break. Figure 3 It can be seen that the FeCrAl-based alloy prepared by the present invention can reach a yield strength of 725Mpa at room temperature, a tensile strength of about 934Mpa, and an elongation of about 14.6%, which is much better than the tensile strength of 521Mpa of the commercial Zr-4 alloy at room temperature. Under the experimental condition of 400℃, the high-temperature tensile strength of the alloy trial-produced in the present invention is still 632Mpa, which is significantly higher than the 254Mpa of the commercial zirconium alloy, indicating that the mechanical properties of the alloy under normal service conditions are significantly better than the existing commercial zirconium alloys, proving that the FeCrAl-based alloy prepared by the present invention has high strength and plasticity at room temperature and better mechanical properties under high temperature conditions of 400℃.

[0100] Figure 6 TEM image of the precipitation phase of the FeCrAl-based alloy with low Cr and high corrosion resistance prepared in Example 1. Figure 6 It can be seen that the average size of the Fe2Nb precipitate phase is about 50-80nm, and most of them are distributed at the subgrain boundaries. In addition, a large number of nanoscale precipitates can be seen inside the grains, which play a pinning role in the movement of dislocations during the deformation of the material and improve the strength and plasticity of the material. This result is due to the two annealing steps after the warm rolling step. Short-term high-temperature annealing can ensure the appearance of a large number of subgrain boundaries in the grains, avoid the complete recrystallization that may exist in the alloy, and significantly improve the mechanical properties of the material. Long-term low-temperature annealing is conducive to the slow precipitation of the Fe2Nb precipitate phase. By controlling the temperature and time of low-temperature annealing, the average size of the precipitate phase can be controlled within a reasonable range, thereby improving the toughness of the material.

[0101] Figure 7 This is a TEM image of the FeCrAl-based alloy precipitate phase prepared in Comparative Example 7. Figure 8 TEM image of the FeCrAl-based alloy precipitate phase prepared in Comparative Example 8. Figure 7 and Figure 6 It can be seen from the comparison that too long high temperature annealing time will lead to a significant increase in grain size and precipitation phase size, which will lead to a sharp decrease in material strength; Figure 8 and Figure 6 From the comparison, it can be seen that the increase of low-temperature annealing temperature will lead to an increase in grain size and a significant increase in the density of the precipitated phase. As a brittle precipitated phase, the high-density distribution of the Laves phase in the material will increase the risk of brittle fracture during the long-term service of the material.

[0102] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A low-Cr and highly corrosion-resistant FeCrAl-based alloy, characterized in that: The low-Cr and highly corrosion-resistant FeCrAl-based alloy comprises the following components by mass percentage: Cr: 10.1%, Al: 4.9%, Mo: 2.3%, Nb: 1.2%, Si: 0.2%, Ta: 0.15%, Zr: 0.18%, Y: 0.08%, C: ≤0.008%, N: ≤0.005%, O: ≤0.003%, and the balance is iron and unavoidable impurities; The preparation method of the low-Cr and highly corrosion-resistant FeCrAl-based alloy comprises the following steps: weighing each alloy element component according to mass percentage to form a steel billet, hot-rolling the steel billet for multiple passes, and then subjecting the hot-rolled plate to high-temperature solid solution treatment, low-temperature rolling and two-pass annealing treatment, taking out and cooling to room temperature to prepare the low-Cr and highly corrosion-resistant FeCrAl-based alloy.

2. The low-Cr and highly corrosion-resistant FeCrAl-based alloy according to claim 1, characterized in that: The temperature of the high temperature solid solution is 1150-1250° C., and the time is 1.5-3.0 hours.

3. The low-Cr and highly corrosion-resistant FeCrAl-based alloy according to claim 1, characterized in that: The low temperature rolling is performed by warm rolling at 420° C. to a specified thickness, with a rolling ratio of 65%, air cooling after rolling, and then straightening by cold rolling.

4. The low-Cr and highly corrosion-resistant FeCrAl-based alloy according to claim 1, characterized in that: The two-pass annealing treatment includes: the first high-temperature annealing temperature is 1130-1170°C, the annealing time is 15-20s, and then water cooling; the second low-temperature annealing temperature is 600-650°C, the annealing time is 30-60min, and air cooling to room temperature after taking out.

5. Use of the low-Cr and highly corrosion-resistant FeCrAl-based alloy according to any one of claims 1 to 4 in the preparation of nuclear reactor fuel cladding materials, aircraft engine structural materials or power plant steam pipe structural materials.

Citation Information

Patent Citations

  • A heat treatment method for low Cr and high toughness alloy

    CN117187705B

  • Stainless steel alloy, preparation method thereof and stainless steel cladding of fuel assembly

    CN106222577A

  • FeCrAl stainless steel cladding tube and preparation method thereof

    CN115161564A

  • Heat treatment method of low-Cr and high-toughness alloy

    CN117187705A